THE EFFECT OF CELEBRITY ENDORSEMENT ON CONSUMER BEHAVIOUR IN KLANG VALLEY MALAYSIA - Fauzee , Zainab Oumme; Dada, Morakinyo (Electronic Journal of Business and Management, 2021)
Marketers are increasingly utilizing the credibility of celebrities and influencers to drive sales, as they significantly influence social media users, particularly Generation Y. However, many marketers still rely on traditional perspectives and fail to identify the specific attributes needed when endorsing new-media celebrities. This study investigates how celebrity attributes influence online consumer behavior through a quantitative analysis. A sample of 136 respondents in Klang Valley, Malaysia, participated in the survey. The findings revealed that attributes such as credibility and attractiveness of the celebrity are key factors that influence consumer behaviors in the digital space.